A Record of Her School Days: The Diary of Nancy McClellan King - Kaliebe, Mohala (Journal of Juvenilia Studies)

(untitled) (International Society of Literary Juvenilia, 2026)
This Spotlight essay describes Nancy McClellan King's 1915 diary, written in Record of My School Days, a record book printed in the early twentieth century specifically for girls to write about their time in secondary school. The book provides a structure within which Nancy writes and against which she pushes back, renegotiating the allotted space within the record book, making room for a 24-stanza ode to her time at school entitled, simply, “Poem I Made Up.” To read this Record is to watch a young author employ her own agency to adapt and assert herself within models provided for her by adults: the material structure of the book, the literary traditions of her education, and even the expected linear progression of time.